Fixing the future - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
Silicon Valley’s business model has wreaked havoc on the world. Human agency will be crucial to save it The World Wide Web, when it exploded into mainstream culture in the mid-1990’s, promised to democratise information and level a playing field that had become tilted towards the rich and elite. When the United States Congress enacted the 1996 Communications Decency Act to regulate pornographic material on the internet, activist John Perry Barlow wrote A Declaration of the Independence of Cyberspace, urging governments to “leave us alone” in a realm where “anyone, anywhere may express his or her beliefs, no matter how singular, without fear of being coerced into silence or conformity”.